Lipid Abnormalities in Type 2 Diabetes Mellitus Patients –Prospective Cross-sectional Study - Jali2, Rajendra Deginal*, M.B. Hiremath*, M.V. Jali*, Sanjay Kambar1*, Suata M. (Recent Research in Science and Technology, 2010)
Introduction: Diabetic dyslipidemia is the major cause for higher cardiovascular morbidity and mortality. Insulin resistance has been shown to be important in regulating the concentrations of lipoproteins and results in predominant lipid abnormalities. Methodology: Prospective, cross sectional study was undertaken to know the prevalence of dyslipidemia among ambulatory patients with type 2 diabetes mellitus at Diabetes Centre, KLES Prabhakar Kore Hospital & MRC, Belgaum,Karnataka. The details history regarding demographic profile, anthropometric measurements, and life style related factors (tobacco and alcohol consumption) were documented in pretested proforma. Fasting venous sample was collected for measurement of serum lipids and glucose. We referred to National Cholesterol Education Programme (NCEP) -Adult Treatment Panel (ATP) III guidelines for lipid profile analysis. Results: A total of 1112 patients with type 2 diabetics without obvious CVD, renal, hepatic or PVD problems were studied. We found that nearly 80% of the subjects had at least one abnormal lipid parameter. 58.6% males and 41.4% females found to be dyslipidemic (p=0.000). Further, the prevalence of isolated hypercholesterolaemia; males (63.4%), females (36.6%), isolated hypertriglycerdaemia; males (58.9%), females (41.1%), isolated high LDL; males (56.7%), females (43.3%) and isolated low HDL; males (52.7%), females (47.3%) was found. Thus prevalence of fasting isolated abnormal lipid parameters was significantly higher among males with diabetes. Conclusion: Many patients with diabetes remain uncontrolled for dyslipidemia. Efforts at screening, treatment and Life style modification according to current guidelines would help in reducing CVD morbidity and mortality in diabetes dyslipidemic patients.